1990
DOI: 10.1073/pnas.87.12.4742
|View full text |Cite
|
Sign up to set email alerts
|

Preincubation in acid medium increases Na/H antiporter activity in cultured renal proximal tubule cells.

Abstract: Chronic acidosis in vivo leads to an increase in proximal tubule Na/H antiporter activity that persists when the transporter is studied out of the acidotic environment. It is presently not clear whether a decrease in extracellular fluid pH alone is sufficient to elicit this adaptation. The present studies examined the effect of acid preincubation on Na/H antiporter activity in cultured proximal tubule cells. Antiporter activity was examined after a 2-day preincubation in control or acid medium, 1 hr after remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
79
0
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(84 citation statements)
references
References 31 publications
4
79
0
1
Order By: Relevance
“…Thus, the tubule is exposed continuously to a newly generated solution. Alpern and colleagues showed that cultured PT cells that were subjected for 2 d to either metabolic or respiratory acidosis responded by increasing their activity of Na-H exchange, a process that requires new protein synthesis (111). Moreover, this effect, as well as increased expression of NHE3 mRNA, is blocked by overexpressing Csk (112), a natural inhibitor of src kinases.…”
Section: Ooe Co 2 /Hco 3 ϫ Solutionsmentioning
confidence: 99%
“…Thus, the tubule is exposed continuously to a newly generated solution. Alpern and colleagues showed that cultured PT cells that were subjected for 2 d to either metabolic or respiratory acidosis responded by increasing their activity of Na-H exchange, a process that requires new protein synthesis (111). Moreover, this effect, as well as increased expression of NHE3 mRNA, is blocked by overexpressing Csk (112), a natural inhibitor of src kinases.…”
Section: Ooe Co 2 /Hco 3 ϫ Solutionsmentioning
confidence: 99%
“…Chronic acidosis causes several metabolic alterations in the renal proximal tubule, including increased H ϩ secretion (1,5), ammonia synthesis (6), and citrate reabsorption (6,7). These changes in tubule function are associated with changes in the activities of a number of proteins, including the apical membrane Na ϩ /H ϩ antiporter (7), glutaminase and glutamate dehydrogenase (8), and phosphoenolpyruvate carboxykinase (9), which may affect intracellular substrate availability for protein turnover, amino acid metabolism and/or transport, and gluconeogenesis.…”
mentioning
confidence: 99%
“…NHE1 has been shown to be stimulated by acid in both animals and cell culture but this is unlikely to be related to transepithelial transport of H + equivalents. [44][45][46] Chronic adaptation of NHE3 has been described in both the proximal tubule (increased NHE3 activity and protein) and TAL (increased NHE3 protein and transcript) in animals given a sufficient acid load to chronically suppress serum [HCO 3 − ]. 36,[47][48][49][50][51][52][53] Presently it is unclear whether the signals and mechanisms responsible for increased NHE3 are the same for the proximal tubule and TAL.…”
Section: Adaptation To Metabolic Acidosismentioning
confidence: 99%